Diagnostic test validation: cochlear hydrops analysis masking procedure in Ménière's disease - Ordóñez-Ordóñez, Leonardo Elías; Rojas-Roncancio, Eveling; Hernández-Alarcón, Víctor; Jaramillo-Safón, Rafael; Prieto-Rivera, Jose; Guzmán-Durán, Jose; Lora-Falquez, Jose; Escobar, Marcela; Angulo-Martínez, Esther Sofía (Otology & neurotology, 2009)
To determine the diagnostic value of the cochlear hydrops analysis masking procedure (CHAMP) in patients with definite Ménière's disease. Prospective validation study for a diagnostic test, study phase 2. Tertiary referral centers. Subjects with definite Ménière's disease (Group 1), differential diagnosis (Group 2: another audiovestibular diseases or neurologic disorders), and normal hearing (Group 3) were included. Sample sizes were calculated. Study test (CHAMP) was compared with the current clinical criterion standard described by the guidelines of the American Academy of Otolaryngology-Head and Neck Surgery. Sensitivity, specificity, and other indicators of diagnostic validation. One hundred ten cases completed the follow-up, and their results are presented. Sensitivity at 31.3% and specificity at 100% were found in subjects with definite Ménière's disease, features that are more helpful in confirming the diagnosis than in rejecting it. Group 1 showed significantly shorter latency delays than Groups 2 and 3 (p < 0.001). If definite Ménière's disease is suspected, an abnormal result confirms the diagnosis; however, a normal result does not rule out the Ménière's disease diagnosis.